2015
DOI: 10.1371/journal.pone.0134328
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evolutionary and Expression Analysis of FCS-Like Zinc finger Gene Family Yields Insights into Their Origin, Expansion and Divergence

Abstract: Plant evolution is characterized by frequent genome duplication events. Expansion of habitat resulted in the origin of many novel genes and genome duplication events which in turn resulted in the expansion of many regulatory gene families. The plant-specific FCS-Like Zinc finger (FLZ) gene family is characterized by the presence of a FCS-Like Zinc finger (FLZ) domain which mediates the protein-protein interaction. In this study, we identified that the expansion of FLZ gene family size in different species is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…In an earlier quantitative (q)RT‐PCR study we found that FLZ6 is expressed more in flowers, silique and seedling stages. FLZ10 also showed a very similar expression pattern (Jamsheer K et al ., ). To get a more detailed picture of the tissue‐ and developmental stage‐specific expression patterns we constructed promoter:GUS reporter lines for both the genes (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In an earlier quantitative (q)RT‐PCR study we found that FLZ6 is expressed more in flowers, silique and seedling stages. FLZ10 also showed a very similar expression pattern (Jamsheer K et al ., ). To get a more detailed picture of the tissue‐ and developmental stage‐specific expression patterns we constructed promoter:GUS reporter lines for both the genes (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…flz10.2 showed reduced biomass and lateral root number, but there was no significant change in primary root length, suggesting that the truncated transcript in this line might be functional to some extent. The phylogenetic analysis suggests that FLZ genes originated in terrestrial plants (Jamsheer K et al ., ). The regulation of SnRK1 signalling by FLZ genes might have originated in land plants, which provide an additional layer of control over the SnRK1 signalling in plants (Figure ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The plasticity and adaptability of scaffold proteins are usually achieved by the presence of intrinsically disordered regions (IDRs) in these proteins (16). FLZ proteins show low sequence conservation outside the FLZ domain indicating that these regions might be enriched with disordered regions (6,7). IDRs lack fixed secondary or tertiary structures.…”
mentioning
confidence: 99%